Gait stability of diabetic patients is altered with the rigid rocker shoes. (October 2019) - Ghomian, Banafshe; Naemi, Roozbeh; Mehdizadeh, Sina; Jafari, Hassan; Ebrahimi Takamjani, Ismael; Aghili, Rokhsareh; Machado, José Mendes; Silva, Luís Fernando Sousa Ferreira; Saeedi, Hassan
Abstract: Background: Rigid-rocker shoes may induce gait instability in diabetics, however, this is not clearly investigated. The present study investigates if rigid-rocker shoes influence diabetic gait stability. Methods: Fourteen non-neuropathic and nine neuropathic diabetics, plus eleven healthy young-adults were recruited. Full-body kinematic data was captured during walking. Experimental conditions included barefoot and three rocker-shoe designs according to the rocker angle, apex angle and apex position (R10: 10°, 80°, 60%; R15: 15°, 95°, 52%; R20: 20°, 95°, 60%). Sagittal and frontal stability margin, plus fear of fall were main outcome measures. Findings. Sagittal stability margin was not affected by health, however, was increased with R10 and R15 in non-neuropathic diabetics and healthy individuals (R 2 = 0.16). Variability of sagittal stability margin was not altered in neuropathic diabetics, but was increased with R15 and R20 in healthy participants, with R15 in non-neuropathic diabetics (R 2 = 0.12). Frontal stability margin (R 2 = 0.46) and its variability (R 2 = 0.39) were significantly increased in neuropathic and non-neuropathic diabetics compared to healthy individuals. Frontal stability margin was significantly higher with R15 in neuropathic diabetics, and with R20 in both non-neuropathic and healthy participants. Sagittal and frontal stability margin were strongly correlated with fear of fall in neuropathic diabetics. Interpretations. R15 and R20 might challenge gait stability of diabetics cause them restrict centre of mass motion thereby imposing a tighter control over walking. However, neuropathic diabetics generally walk very cautious due to neuropathy and increased fear of fall. Frontal stability margin, highly affected by health and experimental condition, is a more sensitive indicator of gait stability. Highlights: Rigid rocker shoes increase challenges to the gait stability of diabetic people. The design of the rigid rocker shoe affects gait stability. Frontal margin of stability is a sensitive indicator of gait stability.